Dual-Mode Communication Terminal Technologies Based on LEO Satellite Internet - Yuanjun LUO; Yinrui BAI; Yongguo YAO; Jian SUN (天地一体化信息网络)
This article proposed a fusion and innovative solution - a dual-mode communication terminal, which integrated the advantages of low-orbit satellite communications and terrestrial wireless self-organizing networks to provide flexible communication solutions.The terminal could obtain cluster routing in real time and autonomously switch between satellite channels and ground ad hoc network channels, reduced the pressure on satellite Internet space and ground transmission channels and realized diversified communication needs.Within the self-organizing network, the terminal used the terrestrial wireless self-organizing network to transmit information, established user clusters and maintain routes.When exceeded the boundary of the self-organizing network, the terminal automatically switched to satellite communication mode and maintained the network.This technology is expected to meet the communication needs of various scenarios, including emergency response and rapid on-site deployment.